Proliferation of SARS-CoV-2 B.1.1.7 Variant in Pakistan-A Short Surveillance Account - Umair, Massab; Salman, Muhammad; Rehman, Zaira; Badar, Nazish; Ali, Qasim; Ahad, Abdul; Ikram, Aamer (Frontiers in Public Health, 2021)
The emergence of a more transmissible variant of SARS-CoV-2 (B1.1.7) in the United Kingdom during late 2020 has raised major public health concerns. Several mutations have been reported in the genome of the B.1.1.7 variant in the Spike region that has implications on virus transmissibility and diagnostics. Although the B.1.1.7 variant has been reported by several countries, only three cases have been reported in Pakistan through whole-genome sequencing. Therefore, the objective of the study was to investigate the circulation of B.1.1.7 variant of concern in Pakistani population. We used a two-step strategy for the detection of B.1.1.7 with initial screening through TaqPathTM COVID-19 RT-PCR kit followed by partial spike (S) gene sequencing of a subset of samples having the spike gene target failure (SGTF). A total of 2,650 samples were tested for SARS-CoV-2 and 70.4% (n=1,867) showed amplification of all the 3 genes (ORF, N, and S). Notably, 29.6% (n=783) samples were found to have the SGTF that represented all the four provinces and these cases were detected at low frequency during the first three weeks of January (n=10, n=13, and n=1 respectively). During February, 726 (93%) cases of SGTF were reported with a peak (n=345) found during the 3rd week. Based on the partial sequencing of SGTF samples 93.5% (n=29/31) showed the characteristic N501Y, A570D, P681H, and T716I mutations found in the B.1.1.7 variant. Our findings highlight a potential high prevalence of B.1.1.7 in Pakistan and warrants large scale genomic surveillance and strengthening of laboratory network in the country.